Cyclical menouria syndrome following mid trimester abortion: a case report - Gupta, Pratiksha; Huria, Anju; Mehra, Reeti; Dalal, Usha (Nepal Journal of Obstetrics and Gynaecology, 2010)
Menouia is terminology used for the passage of menstrual blood only in the urine and results from supraisthmic uterovesical fistula. Report here, for the first time is a case of cyclical menouria, that developed after induced mid trimester abortion in a 26 yrs, P2L2A1 which was diagnosed relatively with ease from history, simple selected investigations who underwent successful surgical repair meaning complete resolution of cyclic haematuria. Key words: Menouria; uterovesical fistula; induced abortion DOI: 10.3126/njog.v4i1.3333 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 49-51